From Cooperative to Welfare: Analyzing the Impact of Food Security on the Welfare of Members of Pasir Jaya Cooperative - Astuti, Qoniatul Munji; Rahayu, Heffi Christya; Afrizal, Andi (Strata Social and Humanities Studies, 2025)
This study investigates the impact of food security on the welfare of members of the Pasir Jaya Cooperative, a rural cooperative located in Pasir Luhur Village, Rokan Hulu Regency. Grounded in the collectivist principles embedded in Indonesia’s constitutional and legal frameworks, cooperatives are positioned not only as economic entities but also as agents of social welfare. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation involving 13 key informants. The results reveal that the Pasir Jaya Cooperative plays a significant role in enhancing member welfare by providing access to affordable and stable food supplies. However, several challenges hinder its effectiveness, including limited product availability, slow capital turnover due to installment-based payments, lack of product variety, and inadequate inventory management. These limitations affect both member satisfaction and the cooperative’s ability to sustainably manage food distribution. The study highlights the need for strategic improvements, particularly in the areas of technology-based inventory systems, alternative funding strategies, product diversification, and cooperative education. The findings underscore the strategic relevance of food security as a pathway to improve member welfare and suggest practical measures to strengthen the role of cooperatives in rural economic development.